A bite difficult to heal: Pasteurella multocida induced decompensated hepatic cirrhosis. Issue 3 (4th May 2021) - Patel, Hiren; Patel, Nirali; Patel, Harsh; Chow, Robert Dobbin
ABSTRACT: Pasteurella multocida is a gram-negative bacterium that colonizes domestic animals. It is commonly implicated in bite and scratch wounds, potentially resulting in cellulitis, superficial abscesses, osteomyelitis, or peritonitis. Rarely, it can lead to bacteremia and septic shock in high-risk patients. We present an atypical presentation of Pasteurella multocida bacteremia and sepsis in a patient with stage 4 decompensated cirrhosis. The patient presented with melena and altered mental status with CT imaging showing a heterogeneous nodular liver along with an enlarged portal vein, gastric varices, and ascites consistent with decompensated cirrhosis. The patient was initially managed with intravenous (IV) octreotide and pantoprazole, blood and platelet transfusions, and broad-spectrum antibiotics. Upper endoscopy showed diffuse non-bleeding esophageal and gastric varices, which required band ligation and continued IV octreotide therapy. The infection resolved after a 7-day course of IV ceftriaxone.